Effect of clay turbidity on the growth performance of Macrobrachium rosenbergii (De Man, 1879) - Saw, Gim Leng (2013)
The study was conducted to find out the effect of different clay turbidities on the growth performance of Macrobrachium rosenbergii post-larvae. The study was completed in 3 weeks. The different clay turbidities used were 0 (control), 200 (T1), 400 (T2) and 800 mg/L (T3). A total of 120 post-larvae were stocked in each 30-liter aquarium for all the treatments. Each treatment had four replicates. Analysis was done using one-way ANOVA followed by Duncan multiple range test. Results showed that increase in clay turbidity level up to 800 mg/L did not affect the growth performance of M. rosenbergii post-larvae. Up to a maximum threshold level where growth would begin to be affected, turbidity could help to improve post-larvae survival since it could potentially reduce cannibalism. Diseased post-larvae however would result in severely reduced survival percentages.